Les filles de Karl Marx : lettres inédites (collection Bottigelli) - Perrot, Michelle; Meier, Olga; Trebitsch, Michel; Marx Longuet, Jenny; Marx Aveling, Eleanor (Paris : Albin Michel, 1979)
Bibliotheek François Vercammen
Frans
Monografie